2008
DOI: 10.1021/pr8006232
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Human Colorectal Cancer Using High-Resolution Magic Angle Spinning Nuclear Magnetic Resonance (HR-MAS NMR) Spectroscopy and Gas Chromatography Mass Spectrometry (GC/MS)

Abstract: Current clinical strategy for staging and prognostication of colorectal cancer (CRC) relies mainly upon the TNM or Duke system. This clinicopathological stage is a crude prognostic guide because it reflects in part the delay in diagnosis in the case of an advanced cancer and gives little insight into the biological characteristics of the tumor. We hypothesized that global metabolic profiling (metabonomics/metabolomics) of colon mucosae would define metabolic signatures that not only discriminate malignant from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

42
374
3
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 416 publications
(423 citation statements)
references
References 45 publications
42
374
3
1
Order By: Relevance
“…The use of GC/MS in the metabolic profiling of esophageal cancer (19), colorectal cancer (10,26,27,35), liver cancer (16), bladder cancer (30) and ovarian cancer (32) has been reported, while few studies have investigated the metabolic profiles of GC tissue. This study explored the metabolic fingerprinting of GC tumor specimens and their matched normal mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of GC/MS in the metabolic profiling of esophageal cancer (19), colorectal cancer (10,26,27,35), liver cancer (16), bladder cancer (30) and ovarian cancer (32) has been reported, while few studies have investigated the metabolic profiles of GC tissue. This study explored the metabolic fingerprinting of GC tumor specimens and their matched normal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…OpLs-DA modeling for the observation of overall separation trends between cancer and non-cancer cohorts has been adopted in human colorectal and bladder cancer (26,27,30,35). previous studies indicate that the supervised model is a robust model for discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it enables enriching the biochemical information from a single tissue biopsy, and offers an improved disease assessment. 23 Another area where MACS could also be of benefit, besides human or animal studies, is examination of single small …”
Section: Concluding Remarks 10mentioning
confidence: 99%
“…In previous reports, human colorectal cancer was related to several biomarkers, such as butyrate, acetate, lipids (saturated and unsaturated), cholinecontaining compounds, and amino acids (e.g., leucine, proline, cysteine). 2 The presence of these biomarkers varies depending on the type and species of the sample. For instance, Monleón et al 47 showed that in human fecal water extracts, normal and cancer samples showed different contents of butyrate, acetate, leucine, proline, and cysteine as determined by NMR spectroscopy.…”
mentioning
confidence: 99%
“…For instance, Monleón et al 47 showed that in human fecal water extracts, normal and cancer samples showed different contents of butyrate, acetate, leucine, proline, and cysteine as determined by NMR spectroscopy. Chan et al 2 showed that human tissue samples contained lipids, choline-containing compounds, taurine, scyllo-inositol, glycine, polyethylene glycol, phosphoethanolamine, phosphocholine, lactate, and glucose using HR-MAS NMR analysis. In the present study, we investigated the differences between normal and cancerous colorectal tissue using HR-MAS NMR spectroscopy with two different analysis methods; target profiling and multivariate analysis techniques.…”
mentioning
confidence: 99%